Investigating the Effectiveness of Enhanced Recovery after Surgery (ERAS) Protocols in Improving Postoperative Outcomes and Reducing Hospital Readmission Rates in Patients Undergoing abdominal Surgery - Ali Akbar Shah; Alfatih Mohamed Ahmed Alnajib; Lalji Baldaniya; Halijah Hassan; Parjinder Kaur; Rajesh Sharma; Hafiza Sobia Ramzan; Waqas Sami (Journal of Pharmacy and Bioallied Sciences)
Objectives: The main objective of the study is to determine the effectiveness of enhanced recovery after surgery (ERAS) protocols in improving postoperative outcomes and reducing hospital readmission rates in patients undergoing abdominal surgery. Materials and Methods: This study involves a total of 650 patients who were divided into two groups: the intervention group, which received care according to ERAS protocols, and the control group, which received standard postoperative care. Patients aged >18 years and scheduled for elective abdominal surgery were included in the study. Results: The mean age of patients in ERAS group were 56.4 ± 12.3 years, while in the standard care group 57.1 ± 11.8 years. Out of 650 patients, there were 339 male and 311 female. Patients were selected from different surgery departments. The ERAS group had lower 30-day readmission rates (6.2% vs. 15.4%), quicker mobilization (12.5 vs. 24.8 hours), and faster resumption of oral intake (8.6 vs. 18.2 hours). Pain levels were lower (VAS 3.1 vs. 5.8), and patient satisfaction was higher (89% vs. 74%) in the ERAS group, with all differences being statistically significant. Conclusion: It is concluded that ERAS protocols significantly improve postoperative outcomes, including reducing complications, shortening hospital stays, and lowering readmission rates for patients undergoing elective abdominal surgery.